The status of job burnout and its influence on the working ability of copper-nickel miners in Xinjiang, China - Xuemei Sun; Li Zhang; Chen Zhang; Jiwen Liu; Hua Ge (BMC, 2020)
Abstract Background Job burnout is increasingly common among occupational groups, and it is evolving into a new occupationally harmful phenomenon. The purpose of this study was to investigate the status of job burnout and its influence on the working ability of copper-nickel miners in Xinjiang, China, and to provide a theoretical basis for alleviating job burnout and improving the working ability of copper and nickel miners. Methods A cross-sectional survey was carried out in June 2017 to September 2018 in Hami City, Xinjiang Autonomous Uygur Region, China. According to the main production process stratification of copper-nickel ore (mining unit, beneficiation unit, smelting unit), a self-administered questionnaire survey on the general situation of miners was conducted on the basis of the Chinese Maslach Burnout Inventory and Work Ability Index Questionnaire among 1400 miners registered in the human resources department of copper and nickel mines by stratified cluster sampling. Results There were 1014 miners with different degrees of burnout, accounting for 80.86% of the total: 432 people reported mild burnout (34.45%), 516 reported moderate burnout (41.15%), and 66 reported high burnout (5.26%). There were significant differences in the degree of burnout according to sex, age, education level, monthly income, and work unit (p < 0.05). The level of male burnout was higher than that of females. Miners aged 35-40 years, with a high-school education, a monthly income of less than 2500 yuan, and who belonged to the smelting unit had the highest job burnout.There were significant differences in working ability among miners with different burnout level (p < 0.01). Partial correlation analysis showed that work ability was negatively correlated with emotional exhaustion, reduced sense of achievement, and total burnout score (p < 0.001). Multinomial logistic regression analyses showed that the education level, professional title,work units and job burnout level had a pronounced impact on the working ability of miners (p < 0.001); The reduced level of education, primary title, smelting unit, and the increase in job burnout are risk factors for the reduction of working ability. Conclusions Our results indicate that job burnout is common among copper and nickel miners. Furthermore, working ability decreases with an increase in job burnout, and reducing job burnout can improve the working ability of copper and nickel miners.